Pelatihan Motivasi dan Manajerial sebagai Upaya Penguatan Kapasitas Perempuan Penjahit Tulungagung - Nurazizah, Fatwa Berlianda; Isnaini, Santi (PELITA NUSA TENGGARA, 2026)
This article presents the results of a community-based capacity building project for women sewing communities in Tulungagung through the development of independent production houses in partnership with an environmentally friendly bag industry. The project responded to persistent constraints in managerial capacity, production facilities, and group institutional structures that limited women’s ability to move from casual piece-rate workers to community-based entrepreneurs. A project-based research approach was implemented through stages of situation analysis, motivational and managerial training, technical production training, formation of production units, and evaluation using pre–post tests, observation, and process documentation. The findings show that all participants successfully formed independent production houses with simple work structures and SOPs, supported by raw material facilities and production equipment from Tulipbag as the main partner. At least one independent production cycle was completed by each group, from planning and role division to administrative recording and reporting to the partner. Significant improvements were observed in motivation, understanding of women’s economic roles, and managerial skills, with Longwe’s framework indicating strong achievements in access to training, managerial control, and collective performance in production tasks. The model offers practical implications for women’s economic empowerment, industry–community partnerships, and the replication of community-based production houses in other creative industry settings.